Managing global health projects in low and middle income countries a practical guide - Robinson, Paul, 1954 May 9- (Abingdon, Oxon ; New York, NY : Routledge, 2024)
With over 30 years of experience in global health programming and teaching, the author offers practical and insightful guidance in this unique book for managing global health projects in resource-constrained settings. Beginning with an overview of fundamental principles, the book delves deeply into a nuts and bolts' approach to health project management. From building project teams and developing detailed activity plans to evaluating health projects and report writing, this book brings the readers a wealth of knowledge they can use to manage health projects. Besides a list of key takeaways and discussion questions, each chapter features a case study exercise from real life situation where readers can picture themselves as project managers, sharpening their understanding of concepts and strategies. Timely and original, this book is an essential resource for university students of global health courses preparing to manage global health projects in low- and middle-income countries, as well as for newly engaged project managers.
Keywords: Medical care; MEDICAL / Public Health; HEALTH & FITNESS / Health Care Issues